2008
DOI: 10.1364/ao.47.002414
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence-induced channel crosstalk in an orbital angular momentum-multiplexed free-space optical link

Abstract: A multichannel free-space optical (FSO) communication system based on orbital angular momentum (OAM)-carrying beams is studied. We numerically analyze the effects of atmospheric turbulence on the system and find that turbulence induces attenuation and crosstalk among channels. Based on a model in which the constituent channels are binary symmetric and crosstalk is a Gaussian noise source, we find optimal sets of OAM states at each turbulence condition studied and determine the aggregate capacity of the multich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
232
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(240 citation statements)
references
References 36 publications
8
232
0
Order By: Relevance
“…Previous theoretical studies of the effects of atmospheric turbulence on the OAM modes have considered the effect of turbulence on the detection probability of OAM modes [6,11,12], the attenuation and crosstalk among multiple OAM channels [13] and the decay of entanglement for bipartite qubits [14,15]. These studies are all based on the Paterson model using a single phase screen [6] with the exception of the analytical study presented in [15] and the numerical study in [13] which are both based on a multiple phase screen approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous theoretical studies of the effects of atmospheric turbulence on the OAM modes have considered the effect of turbulence on the detection probability of OAM modes [6,11,12], the attenuation and crosstalk among multiple OAM channels [13] and the decay of entanglement for bipartite qubits [14,15]. These studies are all based on the Paterson model using a single phase screen [6] with the exception of the analytical study presented in [15] and the numerical study in [13] which are both based on a multiple phase screen approach.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are all based on the Paterson model using a single phase screen [6] with the exception of the analytical study presented in [15] and the numerical study in [13] which are both based on a multiple phase screen approach.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the performance of OAM-based MUX/DEMUX technology for long-distance FSO, we model the OAM beams' propagation in an atmosphere based on the Kolmogorov turbulence theory. [29][30][31][32][33] We take the random intensity and phase perturbation of OAM beams into account and calculate the crosstalk among the OAM states. We define S mn as the percentage of beam energy transferred from the OAM state m to n. While m5n, S mn is the power remaining in the original OAM state m; while m?n, S mn is the crosstalk between OAM states m and n. We define C 2 n as the refractive-index structure parameter with a unit of m 22/3 , which is related to the strength of turbulence in the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…And the nonuniform temperature and air pressure in the atmosphere will cause refractive index change in the transmission path, resulting in the distortion of wavefront phase. The distortion on phase wavefront is extremely harmful for OAM communication, because the OAM demultiplexing is based on the spiral phase distribution [23]. Some previous works have suggested that the refractive index inhomogeneity will result in channel crosstalk among different OAM channels.…”
Section: The Atmospheric Turbulence For Vortex Beam Propagationmentioning
confidence: 99%